Levels, correlates, and differences in human, physical, and financial assets brought into marriages by young Guatemalan adults - Quisumbing, Agnes R.; Behrman, Jere R.; Maluccio, John; Murphy, Alexis; Yount, Katherine M. (SAGE Publications, 2005)
This article examines marriage patterns among individuals who participated as children in a nutrition supplementation trial in Guatemala and were followed up in 2002–04, at ages 25–42 years. Of all 1,062 known and alive couples, 735, or 69%, responded fully to the marriage assets questionnaire. Focus of the analysis is on the birth cohorts born prior to 1974, a total of 1,058 intervention participants, among whom four-fifths of men (82%) and of women (78%) were married at the time of the 2002–04 survey. Basic patterns are examined in current marital status, age at first marriage and related milestones, human capital assets brought to marriage (e.g., schooling attainment, cognitive ability, literacy, and pre-marital work experience), and physical assets and savings accounts brought to marriage. Measures of husbands' human capital at marriage are positively correlated with wives' human capital, but are consistently higher. Husbands also bring substantially more physical and financial assets than wives. A number of interesting patterns emerge, including (1) changes in the composition of assets that women bring to marriage from physical to human assets, (2) declining gaps in age and premarital work experience between husbands and wives, and (3) increasing gaps in schooling attainment and cognitive ability between husbands and wives. Given conflicting directions of change in spousal gaps in human, physical and financial assets, their net effect on changes over time in the bargaining power of husbands and wives is uncertain and deserves further investigation.